Generalized Landauer–Datta–Lundstrom Model in Application to Transport Phenomena in Graphene - Kruglyak, Yu. A.; Strikha, M. V. (Ukrainian Journal of Physics, 2019)
The generalized model of electron transport in the linear response regime developed by R. Landauer, S.Datta, and M. Lundstrom (LDL model) with application to the resistors of any dimension, any size, and arbitrary dispersion working in the ballistic, quasiballistic, or diffusion regimes is summarized in a tutorial review article for the reseachers and universities’ teachers and students. The peculiarities of the electron mobility, as well as the dissipation of heat and the voltage drop in ballistic resistors, are also under consideration. On the basis of the LDL transport model, the characteristics of graphene such as the density of electronic states, dependence of the concentration of carriers on the gate voltage, dependence of the number of modes on the energy, maximum conductivity value, various mechanisms of scattering of carriers and the corresponding mobility determined through the Drude formula, cyclotron frequency, effective mass of carriers, frequency limits for a graphene FET, function of the density of phonon states, and relative contribution of electrons and phonons to the thermal conductivity are discussed.